MicroRNA-143 is associated with the survival of ALDH1+CD133+ osteosarcoma cells and the chemoresistance of osteosarcoma. (July 2015) - Zhou, Jiahui; Wu, Song; Chen, Yuxiang; Zhao, Jingfeng; Zhang, Kexiang; Wang, Jianlong; Chen, Shijie
This study investigated the role of miR-143 in the chemoresistance of osteosarcoma tumor cells and the associated mechanisms. Real-time PCR was used to measure miR-143 levels. Western blot was used to detect protein expression. Cell proliferation was analyzed by MTT assay and Matrigel colony formation assay. Forced miR-143 expression was established by adenoviral vector infection. Cell death was detected by Hoechst33342 staining. Loss of miR-143 expression was observed in osteosarcomas, which correlated with shorter survival of patients with osteosarcomas underlying chemotherapy. In chemoresistant SAOS-2 and U2OS osteosarcomas cells, miR-143 levels were significantly downregulated and accompanied by increases in ATG2B, Bcl-2, and/or LC3-II protein levels, high rate of ALDH1 + CD133 + cells, and an increase in Matrigel colony formation ability. H2 O2 upregulated p53 and miR-143, but downregulated ATG2B, Bcl-2, and LC3-I expression in U2OS cells (wild-type p53) but not in SAOS-2 (p53-null) cells. Forced miR-143 expression significantly reversed chemoresistance as well as downregulation of ATG2B, LC3-I, and Bcl-2 expression in SAOS-2- and U2OS-resistant cells. Forced miR-143 expression significantly inhibited tumor growth in xenograft SAOS-2-Dox and U2OS-Dox animal models. Loss of miR-143 expression is associated with poor prognosis of patients with osteosarcoma underlying chemotherapy. The chemoresistance of osteosarcoma tumor cells to doxorubicin is associated with the downregulation of miR-143 expression, activation of ALDH1 + CD133 + cells, activation of autophagy, and inhibition of cell death. miR-143 may play a crucial role in the chemoresistance of osterosarcoma tumors.